1989
DOI: 10.1007/bf03350002
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of pseudohyperaldosteronism from carbenoxolone

Abstract: Carbenoxolone is a derivative of glycyrrhetinic acid used for the treatment of peptic ulcer and gastritis, with salt and water retention a very common side-effect. To investigate this drug-induced pseudohyperaldosteronism we have studied 6 male volunteers before, during and after treatment with carbenoxolone for 7 days. Serum, urinary and sweat electrolytes values were consistent with a mineralocorticoid-like effect of drug administration. PRA was suppressed, and plasma cortisol and aldosterone progressively d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…hypovolemia, suppressed renin activity and decreased aldosterone levels. The biochemical abnormal ities are the same as in liquorice-induced hypertension 114], whereas carbenoxolone fails to induce any change in the F/E metabolite ratio, in spite of an overall decrease in F metabolite [ 15] which mimics the findings of type 2 AME syndrome 113].…”
Section: Apparent Mineralocorticoid Excess Syndromementioning
confidence: 65%
“…hypovolemia, suppressed renin activity and decreased aldosterone levels. The biochemical abnormal ities are the same as in liquorice-induced hypertension 114], whereas carbenoxolone fails to induce any change in the F/E metabolite ratio, in spite of an overall decrease in F metabolite [ 15] which mimics the findings of type 2 AME syndrome 113].…”
Section: Apparent Mineralocorticoid Excess Syndromementioning
confidence: 65%
“…CBX can inhibit the enzyme complex 11-␤-hydroxysteroid dehydrogenase and significantly suppress the reninaldosterone system (12). The partial attenuation of 11-␤-hydroxysteroid dehydrogenase activity is also believed to contribute to the suppression of PRA and to the decrease of plasma cortisol and aldosterone (1). The literature has reported that CBX, by inhibiting 11-␤-hydroxysteroid dehydrogenase type 1, may decrease the amount of active glucocorticoid in the brain and, as a result, improve verbal fluency in elderly healthy men (aged 55-75; Ref.…”
Section: Discussionmentioning
confidence: 99%
“…81 • Radioreceptorassay for plasma mineralocorticoid receptor activity. 84,96,97 • Binding of aldosterone to MR in kidney cytosol and mononuclear leukocytes. 18 • Urinary tetrahydrocortisol (THF), tetrahydrocortisone (THE), allo-THF, cortisol and cortisone; with calculation of the ratios THF+alloTHF/THE and cortisol/cortisone.…”
Section: Table 1 Methods That Evaluate the Effect Of Aldosterone And mentioning
confidence: 99%
“…By means of this method, the in vivo interaction of licorice and carbenoxolone metabolites with MR was investigated in the plasma of treated subjects. 84,85,97 In recent years, new methods have been developed that evaluate in vitro gene expression.…”
Section: Table 1 Methods That Evaluate the Effect Of Aldosterone And mentioning
confidence: 99%
See 1 more Smart Citation